Individuals’ compassion and organizational inclusiveness: Case studies of Japanese BCtA companies fighting for global health - KYOKO TOKUDA (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: This paper looks at the employees of hybrid organizations from the perspective of the theory that people’s actions have a profound impact on the nature of those organizations and institutions. It demonstrates how these workers are essential for assisting the world’s poorest people in developing nations. Choosing which subset of the population to market to can be complicated by factors at the level of the organization, such as the nature of the business’s structure, strategies, and products.Method: The sample was selected from among the BCtA member companies in Japan that are engaged in inclusive business in the area of global health. Three companies’ employees were surveyed using a Qualtrics online survey. In addition, respondents were asked to rate their level of risk aversion on a scale from "very risk averse" to "not at all" and their willingness to go above and beyond to formally or informally help the extremely poor.Findings: The most compassionate leader and the most welcoming company culture came together to form Company A. Comparatively, the least compassionate respondent worked for Company B and had no personal experience with marginalized groups. His risk aversion was lower than average, and he was willing to help the poorest of the poor if the financial hit could be absorbed elsewhere.Implications/Novel Contribution: This essay aims to show how compassion on a personal level affects the availability of goods and services for the most vulnerable people in developing nations. This research explores the significance and limitations of the three individuals’ compassion-driven efforts to involve the extreme poor in their business processes by conducting an online survey of three Japanese multinational companies certified as members of the United Nations-led Business Call to Action (BCtA) fighting for global health.